1954
DOI: 10.1515/znb-1954-0410
|View full text |Cite
|
Sign up to set email alerts
|

Zur Bestimmung der Amino-Endgruppe im Tabakmosaikvirus

Abstract: Nach Abspaltung der Nucleinsäure aus dem Tabakmosaikvirus mit Trichloressigsäure konnte Prolin als Amino-Endgruppe sowohl nach dem Dinitrophenyl-Verfahren als auch durch Abbau mit Phenylisothiocyanat nachgewiesen werden. Im nucleinsäure-haltigen Protein ist diese Endgruppe nicht zu fassen. Ihre Freisetzung beruht nicht auf einer Hydrolyse der Peptidkette durch Trichloressigsäure, denn1. wird die Zahl der Endgruppen nicht erhöht, wenn man die Behandlung mit Trichloressigsäure auf längere Zeit ausdehnt,2. bewirk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1955
1955
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In TMV-Hg, mercury in the form of -Hg-CH 8, was bound to the extent of one atom to approximately 20,000 molecular weight of virus. Chemical investigations have shown that TMV protein is built up of sub-units of molecular weight 17,000-18,000 (Harris & Knight, 1952Schramm & Braunitzer, 1953;Braunitzer, 1954;Schramm, Braunitzer & Schneider, 1954). The TMV-Hg preparation therefore contains nearly one mercury atom to each sub-unit.…”
Section: The Heavy-atom Derivativementioning
confidence: 99%
“…In TMV-Hg, mercury in the form of -Hg-CH 8, was bound to the extent of one atom to approximately 20,000 molecular weight of virus. Chemical investigations have shown that TMV protein is built up of sub-units of molecular weight 17,000-18,000 (Harris & Knight, 1952Schramm & Braunitzer, 1953;Braunitzer, 1954;Schramm, Braunitzer & Schneider, 1954). The TMV-Hg preparation therefore contains nearly one mercury atom to each sub-unit.…”
Section: The Heavy-atom Derivativementioning
confidence: 99%